2002
DOI: 10.1007/s00421-002-0598-0
|View full text |Cite
|
Sign up to set email alerts
|

Can increased intra-abdominal pressure in humans be decoupled from trunk muscle co-contraction during steady state isometric exertions?

Abstract: The purpose of the present study was to investigate whether increased intra-abdominal pressure (IAP) can be achieved without elevating the overall trunk muscle co-contraction that causes increased spine compression force. Ten subjects performed isometric trunk flexion, extension, and lateral bending exertions while generating 0%, 40% and 80% of their maximal IAP or while co-contracting trunk muscles without consciously raising IAP. An additional three subjects performed a variety of ramp IAP, co-contraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 27 publications
4
38
0
1
Order By: Relevance
“…Because instability cannot be overcome by the contralateral TrA/IO, the ipsilateral TrA/IO begins to contract along with the contralateral TrA/IO to counterbalance the rotation force toward the ipsilateral side and to improve lumbar stability by increasing intra-abdominal pressure via bilateral TrA/IO contractions. 1,[27][28][29][30] These findings are also thought to be elicited by a diagonal trunk rotation moment; the ipsilateral EO and contralateral TrA/IO contract together to counterbalance the ipsilateral rotation moment on a round foam roll. However, we think further research is needed to clarify the exact mechanism for greater contralateral than ipsilateral TrA/IO activity.…”
Section: Discussionmentioning
confidence: 94%
“…Because instability cannot be overcome by the contralateral TrA/IO, the ipsilateral TrA/IO begins to contract along with the contralateral TrA/IO to counterbalance the rotation force toward the ipsilateral side and to improve lumbar stability by increasing intra-abdominal pressure via bilateral TrA/IO contractions. 1,[27][28][29][30] These findings are also thought to be elicited by a diagonal trunk rotation moment; the ipsilateral EO and contralateral TrA/IO contract together to counterbalance the ipsilateral rotation moment on a round foam roll. However, we think further research is needed to clarify the exact mechanism for greater contralateral than ipsilateral TrA/IO activity.…”
Section: Discussionmentioning
confidence: 94%
“…One possible cause for this could be the absence of intra-abdominal pressure and intrathoracic pressure from the model [4,57,58]. Prior studies have shown that both intra-abdominal pressure and intrathoracic pressure are elevated during heavy lifting and other strenuous activities [48,59], and these pressures could act to unload the thoracic and lumbar spines [58]. Although thoracic IDP was overpredicted by the model for these heavy lifting activities, lumbar IDP was not.…”
Section: Discussionmentioning
confidence: 99%
“…Recall that in our model the movement oscillations describe the intra-abdominal pressure that is known to increase the intrathoracic pressure (Cholewicki et al 2002). These oscillations may be specified by their amplitudes corresponding to the maximal variation of muscle contraction and by the offset (M 0 ) around which these oscillations occur.…”
Section: Dynamicsmentioning
confidence: 99%